THE DYNAMICS OF LEARNING DIFFICULTIES AMONG ELEMENTARY SCHOOL CHILDREN IN PALM OIL PLANTATION AREAS: A CASE STUDY OF THE SOCIAL ENVIRONMENT AND LEARNING MOTIVATION IN SUMBER AGUNG VILLAGE - Jamiatul Aini; Muhammad Iqbal Birsyada (SOSIOEDUKASI, 2026)
The education of children in plantation areas often faces unique systemic and social challenges. This study aims to analyze the dynamics of learning difficulties among elementary school students in oil palm plantation areas, with a specific focus on the social environment and learning motivation in Sumber Agung Village. This study employs a qualitative approach using a case study design. Research data were collected through in-depth interviews with students, parents, and teachers, as well as field observations and documentation. The results indicate that the social environment—characterized by parents working as plantation laborers and limited educational facilities—significantly influences students’ perceptions of formal education. Low learning motivation is driven by a lack of academic supervision at home and a prevailing mindset that manual labor is the primary economic pathway. Additionally, the physical distance between plantation housing and schools contributes to student fatigue. This study concludes that learning difficulties in Sumber Agung Village are not merely pedagogical issues but are deeply rooted in the socio-economic structure of the plantation environment. Integrated interventions by the government and plantation companies are needed to improve the educational support system and parental involvement.